ANALYSIS OF METHODOLOGICAL ASPECTS AND CURRENT ASSETS OF COMMERCIAL BANKS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The third direction of the "Development Strategy", aimed at the development and liberalization of the economy, is to deepen the reform of the banking system and ensure stability, increase the level of capitalization and deposit base of banks, strengthen their financial stability and reliability, promising investment projects and small businesses and private entrepreneurship, including further expansion of lending [1].